An exploratory study of behavioural finance insights in the Small, Medium and Micro-Enterprise creditworthiness assessment process - Esekow, Jeremy (College of Accounting, 2014)
Financial institutions are often reluctant to lend to smaller entrepreneurs due to perceived information asymmetry and lack of available collateral. At the nascent and new entrepreneurial levels, it is generally more difficult for loan applicants to provide the information required to secure the necessary funds. Inadequate financial information coupled with uninformative credit histories heighten the information opacity thus diminishing the entrepreneur's prospects of securing loan funding. Viable entrepreneurial projects may therefore remain unfunded largely due to uncertainty rather than riskiness. This study therefore highlights the creditworthiness assessment process and seeks to address the information opacity problem by looking to alternative sources of entrepreneurial information that may aid the loan officer.